Pengaruh Kualitas Produk, dan Harga Mempengaruhi Minat Beli Produk Skincare Avoskin di Shopee - Nazhifah Setiawan, Nisrina; Lina Situngkir, Tiar (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study is to investigate price, product quality on buying interest in avoskin skincare products in the shopee marketplace. This study employs verification and descriptive research methodologies, utilizing quantitative approaches. Respondents taken in this study were 400 respondents, the research determined the respondents taken based on the criteria of avoskin shop official consumer followers in shopee. The study found that price, and product quality affect buying interest significantly. The study also found that the variables of product quality and price on purchase intention with gender as a moderating variable on avoskin products were unable to moderate the influence of product quality variables, and purchase intention on price.